Principal Management Model in Quality Assurance at Vocational High School - Hamengkubuwono Hamengkubuwono (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to determine the principal management model in quality assurance at SMK IT Khoiru Ummah which is a relatively new school but has been able to compete in terms of academic and non-academic achievements. The success achieved is not only at the district level but also at the provincial to national and international levels. This is not only raising the image of education but more importantly being able to optimally develop the talents and interests of students, potential personnel to other potentials that exist in schools. Besides, it is expected to be a reference for several other schools to be used as models. The key to this success is because one of them is the ability of the principal to implement a quality management model that is committed and with high integrity, namely by making, providing report cards for every personnel involved in managing the school. The report cards that are distributed and evaluated every semester have measurable and operational indicators so that they are easy to assess, score and interpret. The indicators in the report cards are socialized at the beginning of each school year after evaluating the overall management phase. This report card becomes feedback for the principal and the foundation to take policies for improvement.